THE INFLUENCE OF SOCIAL MEDIA ON IMPULSIVE BUYING - Ni Wayan Sukmawati Puspitadewi; Fathin Fadhilah (PSIKOSAINS (Jurnal Penelitian dan Pemikiran Psikologi), 2024)
Background: There has been an increase in internet usage and e-commerce users in early 2021. Objective: to determine the effect of social media on impulsive buying. Method: using quantitative correlational methodology. Subjects were 330 respondents, Pearson product moment correlation analysis. Result: coefficient value of 0.448, significance value of 0.001. Social media has a significant effect on impulsive buying with an explained variance of 0.200 (20%). Conclusion: social media has an effect on impulsive buying